Current Research and Potential Applications of the Concealed Information Test: An Overview - Ben-Shakhar, Gershon (Frontiers in Psychology, 2012)
Research interest in psychophysiological detection of deception has significantly increased since the September 11 terror attack in the USA. In particular, the concealed information test (CIT), designed to detect memory traces that can connect suspects to a certain crime, has been extensively studied. In this paper I will briefly review several psychophysiological detection paradigms that have been studied, with a focus on the CIT. The theoretical background of the CIT, its strength and weaknesses, its potential applications as well as research finings related to its validity (based on a recent meta-analytic study), will be discussed. Several novel research directions, with a focus on factors that may affect CIT detection in realistic settings (e.g., memory for crime details; the effect of emotional stress during crime execution) will be described. Additionally, research focusing on mal-intentions and attempts to detect terror networks using information gathered from groups of suspects using both the standard CIT and the searching CIT will be reviewed. Finally, implications of current research to the actual application of the CIT will be discussed and several recommendations that can enhance the use of the CIT will be made.